Comb-type polymer, preparation method, electrode slurry, electrode plate and battery

By using a comb polymer containing specific repeating units in the electrode slurry, the cracking problem during the coating of the sheet thick is solved, high dispersion and flexibility are achieved, and battery performance is improved.

CN119875029APending Publication Date: 2025-04-25RUIGU NEW ENERGY (SHANGHAI) MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311819270.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the extreme sheet is prone to cracking when applied thickly, resulting in surface defects, deterioration of battery performance, and lack of a two-in-one functional additive with high dispersion and preventing the extreme sheet from cracking.

Method used

Using a comb polymer containing repeating units I, II and III, through a specific structure and composition, the dispersion of the electrode paste is improved and the electrode sheets are prevented from cracking.

Benefits of technology

The high dispersion and flexibility of the electrode sheet are achieved, cracking problems during thick coating are avoided, and battery performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875029A_ABST
    Figure CN119875029A_ABST
Patent Text Reader

Abstract

The invention relates to a comb-type polymer, a preparation method, electrode slurry, an electrode plate and a battery. Wherein the comb-type polymer contains a repetitive unit I, a repetitive unit II and a repetitive unit III. The preparation method of the comb-type polymer comprises the following steps: S1, reacting reaction raw materials at a first temperature, and dehydrating; and S2, adding an organic solvent, continuously reacting at a second temperature, and dehydrating. The electrode slurry comprises the comb-type polymer. The electrode plate is prepared from the electrode slurry. The battery comprises the electrode plate. The comb-shaped polymer has the effects of improving the dispersibility of the electrode slurry and preventing the cracking of the electrode plate at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a comb-type polymer, a preparation method, an electrode slurry, an electrode pole piece and a battery. Background Art

[0002] With the development of lithium battery technology, thick electrode coating technology has become one of the most popular technology development directions. The development of thick electrode coating can greatly increase the active material load and reduce the ratio of inactive components, thereby increasing the battery energy density and reducing costs.

[0003] However, the current thick coating of pole pieces still faces great technical challenges. When thickly coated, the surface is prone to cracking, resulting in surface defects of the pole pieces, which ultimately deteriorates battery performance. The reason why the pole pieces are prone to cracking when thickly coated is due to the uneven stress distribution of the various components of the slurry.

[0004] At present, the cracking of the electrode after drying can be improved by adding functional additives. For example, patent application CN202011328100.9 solves the problem of electrode cracking during thick coating by using silanol derivative enhancers, but the enhancer has a general dispersing effect on the positive electrode slurry, and additional dispersants need to be added when preparing high solid content.

[0005] It can be seen that there is currently a lack of two-in-one functional additive products on the market that have both high dispersibility and prevent electrode cracking. Summary of the invention

[0006] In order to overcome the defects of the prior art that the functional additives of the electrode sheet cannot simultaneously make the slurry have high dispersibility and prevent the electrode sheet from cracking, the present invention provides a comb-type polymer, a preparation method, an electrode slurry, an electrode sheet and a battery. The comb-type polymer of the present invention has the effects of improving the dispersibility of the electrode slurry and preventing the electrode sheet from cracking.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a comb polymer comprising a repeating unit I, a repeating unit II and a repeating unit III;

[0009] The structural formula of the repeating unit I is shown in formula (I):

[0010]

[0011] In each repeating unit I,

[0012] R1 is each independently hydrogen or methyl;

[0013] R2 is each independently C1-C4 alkylene or carbonyl;

[0014] R3 is each independently C1-C18 Straight chain alkyl, C1-C 18 Isomeric alkyl, C1-C 18 Heteroalkyl, C6-C 18 Aryl or C6-C 18 heteroaryl;

[0015] n is each independently 0-20;

[0016] m is each independently 1-60;

[0017] The structural formula of the repeating unit II is shown in formula (II):

[0018]

[0019] In each repeating unit II,

[0020] R4 and R5 are both hydrogen;

[0021] R6 are each independently hydrogen or methyl;

[0022] R7 is independently or -C≡N;

[0023] The structural formula of the repeating unit III is shown in formula (III):

[0024]

[0025] In each repeating unit III,

[0026] p is each independently 0 or 1;

[0027] R8, R9, R 10 are each independently hydrogen, methyl or a B group;

[0028] The structure of the B group is -R-COX;

[0029] In each B group, R is independently a connecting bond or a C1-C2 alkylene group, and X is independently -OH or a group represented by formula (IV):

[0030]

[0031] in,

[0032] Y1 and Y2 are each independently hydrogen or a bond connected to the carbonyl group in any B group; Y1 and Y2 are not hydrogen at the same time;

[0033] L is 0 or 1, and k is an integer of 1-6.

[0034] In the present invention, "in each ..., ... are each independently ..." means that in the molecular chain of the comb polymer, in different repeating units represented by the same general formula, the groups represented by the same symbol may be the same or different.

[0035] For example, "in each repeating unit I, R1 is independently hydrogen or methyl" means that in the molecular chain of the comb-type polymer, in different repeating units I represented by formula (I), R1 may be the same or different; in the same repeating unit I, the selection of R1, R2, and R3 does not affect each other. Similarly, each repeating unit II and each repeating unit III have the above meanings.

[0036] For another example, it is also necessary to explain that the meaning of "in each B group, R is independently a connecting bond or a C1-C2 alkylene group, and X is independently -OH or a group represented by formula (IV)" is that in the molecular chain of the comb-type polymer, in different repeating units III represented by formula (III), "R, X" in each B group may be the same or different.

[0037] In the present invention, the nitrogen atom on the group represented by formula (IV) can be connected with one or two carboxyl groups in the repeating unit III to form an amide bond.

[0038] The nitrogen atom on the group represented by formula (IV) can be connected with two carboxyl groups from different repeating units III to form an amide bond, thereby forming a cross-linked structure.

[0039] In the present invention, in the comb polymer, the repeating unit I, the repeating unit II and the repeating unit III may be randomly distributed.

[0040] In the present invention, in the comb-type polymer, the mass proportion of the repeating unit I may be 5%-64% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III.

[0041] In the present invention, in the comb-type polymer, the mass proportion of the repeating unit II may be 0.5%-25% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III.

[0042] In the present invention, in the comb-type polymer, the mass proportion of the repeating unit III may be 35.5%-70% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III.

[0043] In the present invention, the weight average molecular weight of the comb polymer may be 40,000-90,000, for example, 42,887, 44,800, 54,600, 63,400 or 80,400.

[0044] In the present invention, the molecular weight distribution index (PDI) of the comb polymer may be no greater than 2.20, for example, 1.39, 1.63, 1.68 or 1.85.

[0045] In the present invention, in each repeating unit I, R2 is preferably a carbonyl group or a methylene group.

[0046] In the present invention, in each repeating unit I, R3 is preferably C 12 -C 14 Straight chain alkyl or C 13 of isomeric alkyl groups.

[0047] In the present invention, in each repeating unit I, R3 is preferably C1-C 18 of a straight chain alkyl group.

[0048] In certain specific embodiments, in each repeating unit I, R1 is methyl; R2 is carbonyl; n is 0; and R3 is methyl.

[0049] In certain specific embodiments, in each repeating unit I, R1 is a methyl group; R2 is a methylene group; n is 0; and R3 is a methyl group.

[0050] In certain specific embodiments, in each repeating unit I, R1 is methyl; R2 is carbonyl; n is 0; R3 is C 12 -C 14 of a straight chain alkyl group.

[0051] In certain specific embodiments, in each repeating unit I, R1 is methyl; R2 is carbonyl; n is 0; R3 is C 13 of isomeric alkyl groups.

[0052] In certain specific embodiments, in each repeating unit III, R8, R9, R 10 All are hydrogen; p is 0; R is a connecting bond.

[0053] In certain specific embodiments, in each repeating unit III, R8 and R9 are both hydrogen; R 10 is a methyl group; p is 0; and R is a connecting bond.

[0054] In certain specific embodiments, in each repeating unit III, R8, R 10 All are hydrogen; R9 is -COX; p is 0; and R is a connecting bond.

[0055] In certain specific embodiments, in each repeating unit III, R8 and R9 are both hydrogen; R 10 is -COX; p is 0; R is methylene.

[0056] In certain specific embodiments, in each repeating unit III, R8 is -COX; R9, R 10 All are hydrogen; p is 0; R is a connecting bond.

[0057] In certain specific embodiments, in each repeating unit III, R8 is methyl; R9, R 10 All are hydrogen; p is 0; R is a connecting bond.

[0058] In certain specific embodiments, in each repeating unit III, R8, R9, R 10 All are hydrogen; p is 1; and R is a C2 alkylene group.

[0059] In a second aspect, the present invention provides a method for preparing a comb polymer, comprising the following steps:

[0060] S1. The reaction raw materials are reacted at a first temperature and dehydrated;

[0061] S2. adding an organic solvent and continuing the reaction at a second temperature to dehydrate;

[0062] wherein the second temperature is higher than the first temperature; the reaction raw materials include a water-soluble polycarboxylic acid polymer, an organic phosphonic acid compound and water; the water-soluble polycarboxylic acid polymer contains a repeating unit I, a repeating unit II and a repeating unit III';

[0063] The repeating unit I is as described above;

[0064] The repeating unit II is as described above;

[0065] The structure of the repeating unit III' is shown in formula (III'):

[0066]

[0067] In each repeating unit III',

[0068] p' is each independently 0 or 1;

[0069] R8', R9', R 10 ' are each independently hydrogen, methyl or a B' group;

[0070] The structure of the B' group is -R'-COOH;

[0071] In each B' group, R' is independently a connecting bond or a C1-C2 alkylene group;

[0072] The structure of the organic phosphonic acid compound is shown in formula (IV'):

[0073]

[0074] Wherein, L' is 0 or 1, and k' is an integer of 1-6.

[0075] In the present invention, in the water-soluble polycarboxylic acid polymer, the mass proportion of the repeating unit I may be 10%-69% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III'.

[0076] In the present invention, in the water-soluble polycarboxylic acid polymer, the mass proportion of the repeating unit II may be 1%-30% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III'.

[0077] In the present invention, in the water-soluble polycarboxylic acid polymer, the mass proportion of the repeating unit III' may be 30%-60% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III'.

[0078] In the present invention, the weight average molecular weight of the water-soluble polycarboxylic acid polymer may be 10,000-50,000, such as 17,900, 23,121, 26,300, 27,900 or 33,700.

[0079] In the present invention, the molecular weight distribution index (PDI) of the water-soluble polycarboxylic acid polymer may be no greater than 2.30, for example, 1.71, 2.01, 2.05, 2.12 or 2.27.

[0080] In the present invention, in the water-soluble polycarboxylic acid polymer, the repeating unit I, the repeating unit II and the repeating unit III' may be randomly distributed.

[0081] In the present invention, the organic phosphonic acid compound can be phosphoethanolamine, 2-aminoethylphosphonic acid, 3-aminopropylphosphonic acid or 4-aminobutylphosphonic acid.

[0082] In the present invention, the molar ratio of the water-soluble polycarboxylic acid polymer to the organic phosphonic acid compound can be adjusted based on the final effect of the product, preferably 1:(6-150), more preferably 1:(6-30), for example 1:6.62, 1:21.06, 1:21.77, 1:25.13 or 1:27.87.

[0083] In the present invention, in step S1, the reaction raw materials also include a catalyst.

[0084] Wherein, the catalyst can be p-toluenesulfonic acid, concentrated sulfuric acid or methanesulfonic acid.

[0085] Wherein, the amount of the catalyst used may be 0.5%-1.2% of the total mass of the water-soluble polycarboxylic acid polymer and the organic phosphonic acid compound.

[0086] In the present invention, in step S1, the first temperature may be 80-85°C, for example 80°C.

[0087] In the present invention, in step S1, the reaction time may be 1-3 hours, such as 1 hour or 2 hours.

[0088] In the present invention, in step S1, the vacuum degree of dehydration may not exceed -92 kPa, for example, -88 kPa, -90 kPa or -92 kPa.

[0089] In the present invention, in step S1, the dehydration time may be 1-2 hours.

[0090] In the present invention, in step S2, the organic solvent may be at least one of toluene, xylene, methyl pyrrolidone, propylene glycol methyl ether acetate, butyl acetate and N,N-dimethylformamide.

[0091] In the present invention, in step S2, the second temperature may be 100-120°C, such as 105°C, 110°C or 120°C.

[0092] In the present invention, in step S2, the reaction time may be 1-3 h, such as 1 h or 2 h.

[0093] In the present invention, in step S2, the vacuum degree of dehydration may not exceed -92 kPa, for example, -88 kPa, -90 kPa or -92 kPa.

[0094] In the present invention, in step S2, the dehydration time may be 1-2 hours.

[0095] In the present invention, in step S2, the dehydration may be followed by cooling.

[0096] Wherein, the cooling temperature may be 50°C or below.

[0097] Wherein, after the temperature is lowered, a neutralizing agent may be used for neutralization before discharging. The neutralizing agent may be one or more of lithium hydroxide, potassium hydroxide, sodium hydroxide, ethanolamine, diethanolamine, triethanolamine, isopropanolamine and 2-amino-2-methyl-1-propanol.

[0098] In the present invention, during the reaction, the amine group on the organic phosphonic acid compound can react with one or two carboxyl groups on the monomer M-3.

[0099] The amine group on the organic phosphonic acid compound can react with two carboxyl groups from different monomers M-3 to form a cross-linked structure.

[0100] In the present invention, the preparation method of the water-soluble polycarboxylic acid polymer may include the following steps: in the presence of an initiator and a chain transfer agent, polymerizing the monomer M-1, the monomer M-2 and the monomer M-3 in a solvent. The monomer M-1 may be a compound corresponding to the repeating unit I; the monomer M-2 may be a compound corresponding to the repeating unit II; the monomer M-3 may be a compound corresponding to the repeating unit III', or an acid anhydride formed from the compound corresponding to the repeating unit III'.

[0101] The mass of the monomer M-1 may be 10%-69% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3, for example, 10%, 30%, 40%, 67% or 69%.

[0102] Wherein, the monomer M-1 may be an unsaturated end-capped polyether. The unsaturated end-capped polyether may be polyethylene glycol monomethyl ether methacrylate, methyl end-capped methyl allyl alcohol polyoxyethylene ether, C 12 -C 14 Carbon alcohol polyoxyethylene ether methacrylate, C 12 -C 14 Carbon alcohol polyoxyethylene ether acrylate, isomeric tridecanol polyoxyethylene ether methacrylate, isomeric tridecanol polyoxyethylene ether acrylate, C1-C 18 Alkyl-terminated allyl alcohol polyoxyethylene ether, C1-C 18 Alkyl-terminated methyl allyl alcohol polyoxyethylene ether, C1-C 18 Alkyl-terminated allyl alcohol polyoxypropylene ether or C1-C 18 Alkyl terminated methyl allyl alcohol polyoxypropylene polyoxyethylene ether. The average polymerization degree of the polyether segment in the unsaturated terminated polyether may be 7-10.

[0103] In certain specific embodiments, the monomer M-1 is polyethylene glycol monomethyl ether methacrylate, methyl terminated methyl allyl alcohol polyoxyethylene ether, C 12 -C 14 Carbon alcohol polyoxyethylene ether methacrylate or isomeric tridecanol polyoxyethylene ether methacrylate.

[0104] The molecular weight of the monomer M-1 may be 300-1000, preferably 350-600, such as 350, 400 or 600.

[0105] The mass of the monomer M-2 may be 1%-30%, for example, 1%, 3%, 5%, 10% or 30%, of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3.

[0106] Wherein, the monomer M-2 may be acrylonitrile, vinyl pyrrolidone, vinyl pyridine, vinyl imidazole or 2-acrylamide-2-methylpropane sulfonic acid.

[0107] The mass of the monomer M-3 may be 30%-60% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3, for example, 30%, 55% or 60%.

[0108] Wherein, the monomer M-3 can be acrylic acid Methacrylic acid Maleic anhydride Itaconic acid Fumaric Acid Crotonic acid or β-acryloyloxypropionic acid

[0109] Wherein, the initiator may be at least one of ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide and a water-soluble azo initiator.

[0110] The amount of the initiator used may be 0.1%-1% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3.

[0111] Wherein, the chain transfer agent may be at least one of isopropyl alcohol, mercaptoethanol, thioglycolic acid and mercaptopropionic acid.

[0112] The amount of the chain transfer agent used may be 0.1%-5% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3.

[0113] The initiator, the chain transfer agent, the monomer M-1, the monomer M-2 or the monomer M-3 can be added dropwise in the form of an aqueous solution for a time of 180-210 minutes.

[0114] Wherein, the solvent may be water.

[0115] The polymerization conditions can be selected conventionally in the art.

[0116] The polymerization temperature may be 65-85°C, such as 75°C or 80°C.

[0117] The polymerization time may be 40-80 min, for example 60 min.

[0118] In a third aspect, the present invention provides a comb polymer prepared by the method for preparing a comb polymer as described above.

[0119] In a fourth aspect, the present invention provides an electrode slurry comprising the comb polymer as described above.

[0120] In the present invention, based on 100% of the total solid mass, the electrode slurry may include the following components in proportion by mass: 93%-98% of active material, 1%-4% of conductive agent, 1%-3% of binder and 0.1%-0.5% of the comb polymer.

[0121] The active material may be one or more of lithium iron phosphate, lithium iron manganese phosphate and nickel-cobalt-manganese ternary material.

[0122] The conductive agent may be one or more of conductive graphite, conductive carbon black and conductive carbon nanotubes.

[0123] Wherein, the binder may be PVDF.

[0124] In a fifth aspect, the present invention provides an electrode plate, which is made using the electrode slurry as described above.

[0125] In the present invention, the method for preparing an electrode plate using the electrode slurry can be conventional in the art, and generally comprises: coating the electrode slurry on at least one surface of a current collector, and drying.

[0126] In a sixth aspect, the present invention provides a battery comprising the electrode plate as described above.

[0127] In the present invention, the battery is preferably a lithium-ion battery.

[0128] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0129] The reagents and raw materials used in the present invention are commercially available.

[0130] The positive and progressive effects of the present invention are:

[0131] (1) The comb-type polymer of the present invention contains carboxyl and phosphate functional groups, which can be anchored to the surface of lithium iron phosphate to provide electrostatic repulsion. At the same time, the polyether side chain of the comb-type polymer provides a spatial position, so that the polymer has good dispersibility;

[0132] (2) The comb-type polymer of the present invention has good flexibility due to the presence of a cross-linked structure. The phosphate functional group has good binding force to the carbon coating layer of lithium iron phosphate, the exposed metal on the surface of lithium iron phosphate, and the added metal doping elements, which can make the flexible comb-type polymer evenly distributed on the surface of each component of the slurry, thereby improving the flexibility of the entire electrode and achieving thick coating of the slurry without cracking;

[0133] (3) The water-soluble polycarboxylic acid polymer used in the present invention can further improve the dispersion performance of the comb-type polymer by optimizing the monomer M-2. For example, the selection of acrylonitrile as the monomer M-2 can further improve the electronic conductivity of the polymer. As the amount of acrylonitrile used increases, the dispersion and viscosity stabilization performance of the dispersant can also be optimized. The use of vinyl pyrrolidone, vinyl pyridine, vinyl imidazole and 2-acrylamido-2-methylpropane sulfonic acid can also improve the dispersibility of the polymer, thereby improving the dispersion and viscosity stabilization performance of the comb-type polymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0134] Figure 1 This is a graph showing the gel chromatography characterization results of the water-soluble polycarboxylic acid polymer P1 in Example 1;

[0135] Figure 2 This is a graph showing the gel chromatography characterization results of the comb-type polymer dispersant S1 in Example 1;

[0136] Figure 3 This is a graph showing the gel chromatography characterization results of the polycarboxylic acid polymer K1 in Comparative Example 1;

[0137] Figure 4 This is a photograph of the appearance of the electrode in the effect embodiment after baking. DETAILED DESCRIPTION

[0138] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0139] In the following examples and comparative examples:

[0140] (1) Weight average molecular weight and molecular weight distribution index (PDI)

[0141] The water-soluble polycarboxylic acid polymers in Examples 1-5 were tested for molecular weight using Waters' e2695 GPC, with the mobile phase being a 0.1 mol / L NaNO3 aqueous solution. The comb-type polymers in Examples 1-5 and polymer K1 in Comparative Example 1 were tested for molecular weight using Waters' e2695 GPC, with the mobile phase being a methylpyrrolidone (NMP) solution containing 0.01 mol / L tetrabutylammonium bromide.

[0142] (2) Solid content

[0143] Solid content means the mass percentage of solids in a slurry or solution. For example, in the polymer solutions in Examples 1-5, the solids can be regarded as the prepared polymers. For example, the solids in the positive electrode slurry in Table 3 include the solid weight of lithium iron phosphate, conductive agent, PVDF and the solid weight of the dispersant in the polymer solution.

[0144] Example 1

[0145] 265g of deionized water was added to a 2000ml flask and heated to 80°C. 360g of acrylic acid, 180g of polyethylene glycol monomethyl ether methacrylate with a molecular weight of 400, 60g of acrylonitrile, 5g of mercaptoethanol and 25g of deionized water were uniformly mixed to obtain a monomer mixture. 1.8g of ammonium persulfate was dissolved in 103.2g of deionized water to obtain an initiator solution. The monomer mixture and the initiator solution were added dropwise at 80°C. The monomer mixture was added dropwise for 180min and the initiator solution was added dropwise for 210min. After the addition was completed, the reaction was kept warm for 1h to obtain a water-soluble polycarboxylic acid polymer P1 with a weight average molecular weight of 23121 and a molecular weight distribution index (PDI) of 2.05. Figure 1 shown.

[0146] In a 1000ml flask, add 600g (0.026mol) of water-soluble polycarboxylic acid polymer P1, 50g of deionized water and 92g (0.652mol) of ethanolamine phosphate, stir and heat to 80°C for reaction for 1h, then start vacuum dehydration, and the vacuum degree gradually increases from -60kPa to -90kPa. After vacuuming for 2h, stop vacuuming.

[0147] 450 g of methyl pyrrolidone solvent was added for dilution, the temperature was raised to 110°C and the reaction was continued for 2 h, then dehydrated for 1 h under a vacuum of -88 kPa to -92 kPa, and the temperature was lowered to below 50°C to obtain a polymer solution containing a comb-type polymer dispersant S1 with a solid content of 50%. The weight average molecular weight of the comb-type polymer S1 was 42887, and the molecular weight distribution index (PDI) was 1.39. Figure 2 shown.

[0148] Example 2

[0149] 265g of deionized water was added to a 2000ml flask and heated to 80°C. 300g of acrylic acid, 30g of maleic anhydride, 240g of methyl-terminated methylallyl alcohol polyoxyethylene ether with a molecular weight of 350, 30g of vinyl pyrrolidone, 5g of mercaptoethanol and 25g of deionized water were uniformly mixed to obtain a monomer mixture. 1.8g of ammonium persulfate was dissolved in 103.2g of deionized water to obtain an initiator solution. The monomer mixture and the initiator solution were added dropwise at 80°C. The monomer mixture was added dropwise for 180min, and the initiator solution was added dropwise for 210min. After the addition was completed, the mixture was kept warm for 1h to obtain a water-soluble polycarboxylic acid polymer P2 with a weight average molecular weight of 26300 and a molecular weight distribution index (PDI) of 2.01.

[0150] In a 1000ml flask, add 600g (0.023mol) of water-soluble polycarboxylic acid polymer P2 and 62.1g (0.497mol) of 2-aminoethylphosphonic acid, stir and heat to 80°C for reaction for 1h, then start vacuum dehydration, and the vacuum degree gradually increases from -60kPa to -90kPa. After vacuuming for 2h, stop vacuuming.

[0151] 418 g of toluene was added for dilution, the temperature was raised to 120° C. and the reaction was continued for 1 h, then dehydrated under a vacuum degree of -88 kPa to -92 kPa for 1 h, and the temperature was lowered to below 50° C. to obtain a polymer solution containing a comb-type polymer S2 with a solid content of 50%. The weight average molecular weight of the comb-type polymer S2 was 54,600, and the molecular weight distribution index (PDI) was 1.63.

[0152] Example 3

[0153] 265g of deionized water was added to a 2000ml flask and the temperature was raised to 75°C. 180g of acrylic acid and 414g of C 12 -C 14 Carbon alcohol polyoxyethylene 07 ether methacrylate, 6g vinyl imidazole, 4g mercaptoethanol and 26g deionized water were uniformly mixed to obtain a monomer mixture. 2.4g ammonium persulfate was dissolved in 102.6g deionized water to obtain an initiator solution, and the monomer mixture and the initiator solution were added dropwise at 80°C. The monomer mixture was added dropwise for 180min, and the initiator solution was added dropwise for 210min. After the addition was completed, the mixture was kept warm for 1h to obtain a water-soluble polycarboxylic acid polymer P3 with a weight average molecular weight of 27900 and a molecular weight distribution index (PDI) of 2.27.

[0154] In a 1000ml flask, add 600g (0.022mol) of water-soluble polycarboxylic acid polymer P3 and 63g (0.453mol) of 3-aminopropylphosphonic acid, stir and heat to 80°C for reaction for 1h, then start vacuum dehydration, and the vacuum degree gradually increases from -60kPa to -90kPa. After vacuuming for 2h, stop vacuuming.

[0155] 450 g of xylene was added for dilution, the temperature was raised to 110° C. and the reaction was continued for 2 h, then dehydrated for 1 h under a vacuum of -88 kPa to -92 kPa, the temperature was lowered to below 50° C., 27 g of ethanolamine was added for neutralization, and after stirring evenly, a polymer solution containing the comb-type polymer S3 was obtained, and the solid content thereof was 50%. The weight average molecular weight of the comb-type polymer S3 was 63400, and the molecular weight distribution index (PDI) was 1.85.

[0156] Example 4

[0157] 196g of deionized water was added to a 2000ml flask and heated to 75°C. 240g of methacrylic acid, 120g of β-acryloxypropionic acid, 60g of polyethylene glycol monomethyl ether methacrylate with a molecular weight of 600, 180g of vinyl pyrrolidone, 5g of mercaptoethanol and 115g of deionized water were mixed to obtain a monomer mixture. 2.4g of ammonium persulfate was dissolved in 81.6g of deionized water to obtain an initiator solution. The monomer mixture and the initiator solution were added dropwise at 80°C. The monomer was added dropwise for 180min and the initiator was added dropwise for 210min. After the addition was completed, the reaction was kept warm for 1h to obtain a water-soluble polycarboxylic acid polymer P4 with a weight average molecular weight of 33700 and a molecular weight distribution index (PDI) of 2.12.

[0158] In a 1000ml flask, add 600g (0.018mol) of water-soluble polycarboxylic acid polymer P4 and 70g (0.496mol) of ethanolamine phosphate, stir and heat to 80°C for reaction for 1h, then start vacuum dehydration, and the vacuum degree gradually increases from -60kPa to -90kPa. After vacuuming for 2h, stop vacuuming.

[0159] 420 g of methyl pyrrolidone was added, the temperature was raised to 110° C. and the reaction was continued for 2 h, then dehydrated for 1 h under a vacuum degree of -88 kPa to -92 kPa, and the temperature was lowered to below 50° C. to obtain a polymer solution containing a comb-type polymer S4 with a solid content of 50%. The weight average molecular weight of the comb-type polymer S4 was 80400, and the molecular weight distribution index (PDI) was 1.63.

[0160] Example 5

[0161] 196g of deionized water was added to a 2000ml flask and heated to 75°C. 180g of acrylic acid, 60g of methyl-terminated allyl alcohol polyoxypropylene ether with a molecular weight of 350, 342g of isomeric tridecanol polyoxyethylene 10 ether methacrylate, 18g of 2-acrylamide-2-methylpropanesulfonic acid, 5g of mercaptoethanol and 115g of deionized water were uniformly mixed to obtain a monomer mixture. 2.4g of ammonium persulfate was dissolved in 81.6g of deionized water to obtain an initiator solution. The monomer mixture and the initiator solution were simultaneously added dropwise at 80°C. The monomer mixture was added dropwise for 180min, and the initiator solution was added dropwise for 210min. After the addition was completed, the mixture was kept warm for reaction for 1h to obtain a water-soluble polycarboxylic acid polymer P5 with a weight average molecular weight of 17900 and a molecular weight distribution index (PDI) of 1.71.

[0162] In a 1000ml flask, add 600g (0.034mol) of water-soluble polycarboxylic acid polymer P5, 34g (0.222mol) of 4-aminobutylphosphonic acid and 2g of p-toluenesulfonic acid, stir and heat to 80℃ for 1h, then start vacuum dehydration, and the vacuum degree gradually increases from -60kPa to -90kPa. After 2h of vacuuming, stop vacuuming.

[0163] 420 g of methyl pyrrolidone was added, the temperature was raised to 105° C. and the reaction was continued for 2 h, then dehydrated for 1 h under a vacuum degree of -88 kPa to -92 kPa, and the temperature was lowered to below 50° C. to obtain a polymer solution containing a comb-type polymer S5 with a solid content of 50%. The weight average molecular weight of the comb-type polymer S5 was 44,800, and the molecular weight distribution index (PDI) was 1.68.

[0164] Comparative Example 1

[0165] 265g of methyl pyrrolidone was added to a 2000ml flask and heated to 80°C. 360g of acrylic acid, 180g of polyethylene glycol monomethyl ether methacrylate with a molecular weight of 400, 60g of acrylonitrile, 4g of mercaptoethanol and 26g of methyl pyrrolidone were mixed evenly to obtain a monomer mixture. 1.8g of azobisisobutyronitrile was dissolved in 103.2g of methyl pyrrolidone to obtain an initiator solution. The monomer mixture and the initiator solution were added dropwise at 80°C. The monomer was added dropwise for 180min and the initiator was added dropwise for 210min. After the addition was completed, the reaction was kept warm for 1h to obtain a polymer solution containing polycarboxylic acid polymer K1 with methyl pyrrolidone as solvent and a solid content of 60%. The weight average molecular weight of polymer K1 was 27100, and the molecular weight distribution index (PDI) was 1.88. Figure 3 .

[0166] The main raw materials of Examples 1-5 and Comparative Example 1 are summarized in Table 1 below.

[0167] Table 1

[0168]

[0169] Application Examples

[0170] The polymer solutions obtained in the above embodiments and comparative examples were wet-slurried using a planetary degasser according to the following positive electrode slurry formulation to obtain positive electrode slurry. The blank sample was not added with polymer solution, and the amount of active material was adjusted to 97% as a comparative sample. The data obtained are shown in Table 2-3.

[0171] Table 2 Amount of solid components in positive electrode slurry

[0172]

[0173] Table 3 Amounts of all components of positive electrode slurry

[0174]

[0175] The PVDF is added in the form of 6 wt% PVDF NMP glue. For example, 57.86 g of glue is added, which contains 3.47 g of PVDF.

[0176] The polymer was added in the form of a polymer solution in the examples or comparative examples, i.e., in the comparative slurry, 0.578 g of a polymer solution containing polymer K1 with a solid content of 60 wt % was added, which contained 0.35 g of dispersant K1 solid. Similarly, in slurries 1-5, 0.694 g of a polymer solution containing polymer with a solid content of 50 wt % was added, which contained 0.347 g of polymer solid.

[0177] Effect Example

[0178] The cathode slurry performance in various application cases is tested, including:

[0179] (1) Viscosity test

[0180] The viscosity test was carried out using a digital display rotational viscometer. After the sample was heated to a constant temperature of 25°C, a No. 64 rotor was used. The digital display data at 3 minutes of testing was the viscosity test data. The results are shown in Table 4:

[0181] (2) Pole cracking test

[0182] The obtained positive electrode slurry was coated onto the positive electrode carbon-coated foil using a small automatic coating machine from Shenghua Industrial. The electrode was coated on one side with a coating surface density of 25.5 mg / cm 2 Then the coated foil was placed in a 120°C forced air drying oven and baked for 30 minutes. The cracking of the electrode surface was observed. The results are shown in Table 4 and Figure 4 As shown:

[0183] Table 4 Test results of cathode slurry performance

[0184] Discharge viscosity mPa·s 24h viscosity mPa·s Pole cracking blank 18200 30450 Severe cracking Slurry 1 7360 13860 No cracking Slurry 2 5540 14100 No cracking Slurry 3 6740 13820 No cracking Slurry 4 4640 12500 No cracking Slurry 5 8200 15920 No cracking Comparison slurry 12520 19640 Cracking

[0185] From the test results, it can be seen that the initial viscosity and 24h viscosity of the slurry using the dispersant and the control slurry have been significantly reduced, indicating that the samples have good dispersibility. Among them, compared with the polymer K1 without the grafted phosphate compound added to the control slurry, after adding the comb-type polymer grafted with the phosphate compound in the embodiment to the slurry 1-5, they all showed a significant effect of reducing the slurry viscosity, the dispersion performance was further improved, and the prepared pole pieces no longer cracked. It shows that the grafted phosphate compound not only improves the dispersibility of the polymer, but also the cross-linked structure formed after the phosphate ester capping can solve the cracking problem during the baking process of the pole piece.

Claims

1. A comb polymer, characterized in that It contains repeating unit I, repeating unit II and repeating unit III; The structural formula of the repeating unit I is shown in formula (I): In each repeating unit I, R1 is each independently hydrogen or methyl; R2 is each independently C1-C4 alkylene or carbonyl; R3 is each independently C1-C 18 Straight chain alkyl, C1-C 18 Isomeric alkyl, C1-C 18 Heteroalkyl, C6-C 18 Aryl or C6-C 18 heteroaryl; n is each independently 0-20; m is each independently 1-60; The structural formula of the repeating unit II is shown in formula (II): In each repeating unit II, R4 and R5 are both hydrogen; R6 are each independently hydrogen or methyl; R7 is independently or -C≡N; The structural formula of the repeating unit III is shown in formula (III): In each repeating unit III, p is each independently 0 or 1; R8, R9, R 10 are each independently hydrogen, methyl or a B group; The structure of the B group is -R-COX; In each B group, R is independently a connecting bond or a C1-C2 alkylene group, and X is independently -OH or a group represented by formula (IV): in, Y1 and Y2 are each independently hydrogen or a bond connected to the carbonyl group in any B group; Y1 and Y2 are not hydrogen at the same time; L is 0 or 1, and k is an integer of 1-6.

2. The comb polymer according to claim 1, characterized in that In the comb-type polymer, the repeating unit I, the repeating unit II and the repeating unit III are randomly distributed; And / or, in the comb-type polymer, the mass proportion of the repeating unit I is 5%-64% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III; And / or, in the comb-type polymer, the mass proportion of the repeating unit II is 0.5%-25% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III; And / or, in the comb-type polymer, the mass proportion of the repeating unit III is 35.5%-70% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III; and / or, the comb polymer has a weight average molecular weight of 40,000-90,000, such as 42,887, 44,800, 54,600, 63,400 or 80,400; and / or, the PDI of the comb polymer is no greater than 2.20, for example, 1.39, 1.63, 1.68 or 1.85; And / or, in each repeating unit I, R1, R2, R3, and n each independently satisfy any one of the following conditions ①-⑦: ①R2 is a carbonyl group or a methylene group; ②R3 is C 12 -C 14 A straight chain alkyl or C 13 Isomeric alkyl groups; ③R3 is C1-C 18 A straight chain alkyl group; ④R1 is methyl; R2 is carbonyl; n is 0; R3 is methyl; ⑤R1 is methyl; R2 is methylene; n is 0; R3 is methyl; ⑥R1 is methyl; R2 is carbonyl; n is 0; R3 is C 12 -C 14 A straight chain alkyl group; ⑦R1 is methyl; R2 is carbonyl; n is 0; R3 is C 13 Isomeric alkyl groups; And / or, in each repeating unit III, R8, R9, R 10 , p, and R independently satisfy any one of the following conditions ①-⑦: ①R8, R9, R 10 All are hydrogen; p is 0; R is a connecting bond; ②R8 and R9 are both hydrogen; R 10 is a methyl group; p is 0; R is a connecting bond; ③R8, R 10 are all hydrogen; R9 is -COX; p is 0; R is a connecting bond; ④R8 and R9 are both hydrogen; R 10 is -COX; p is 0; R is methylene; ⑤R8 is -COX; R9, R 10 All are hydrogen; p is 0; R is a connecting bond; ⑥R8 is methyl; R9, R 10 All are hydrogen; p is 0; R is a connecting bond; ⑦R8, R9, R 10 All are hydrogen; p is 1; and R is a C2 alkylene group.

3. A method for preparing a comb-type polymer, characterized in that: It includes the following steps: S1. The reaction raw materials are reacted at a first temperature and dehydrated; S2. adding an organic solvent and continuing the reaction at a second temperature to dehydrate; wherein the second temperature is higher than the first temperature; the reaction raw materials include a water-soluble polycarboxylic acid polymer, an organic phosphonic acid compound and water; the water-soluble polycarboxylic acid polymer contains a repeating unit I, a repeating unit II and a repeating unit III'; The repeating unit I is as described in claim 1 or 2; The repeating unit II is as described in claim 1 or 2; The structure of the repeating unit III' is shown in formula (III'): In each repeating unit III', p' is each independently 0 or 1; R8', R9', R 10 ' are each independently hydrogen, methyl or a B' group; The structure of the B' group is -R'-COOH; In each B' group, R' is independently a connecting bond or a C1-C2 alkylene group; The structure of the organic phosphonic acid compound is shown in formula (IV'): Wherein, L' is 0 or 1, and k' is an integer of 1-6.

4. The method for preparing a comb polymer according to claim 3, characterized in that: The water-soluble polycarboxylic acid polymer meets one or more of the following conditions: ① The mass proportion of the repeating unit I is 10%-69% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III'; ② In the water-soluble polycarboxylic acid polymer, the mass proportion of the repeating unit II is 1%-30% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III'; ③ In the water-soluble polycarboxylic acid polymer, the mass proportion of the repeating unit III' is 30%-60% of the total mass of the repeating unit I, the repeating unit II and the repeating unit III'; ④ The weight average molecular weight of the water-soluble polycarboxylic acid polymer is 10000-50000, for example, 17900, 23121, 26300, 27900 or 33700; ⑤ The PDI of the water-soluble polycarboxylic acid polymer is not greater than 2.30, for example, 1.71, 2.01, 2.05, 2.12 or 2.27; ⑥ In the water-soluble polycarboxylic acid polymer, the repeating unit I, the repeating unit II and the repeating unit III' are randomly distributed; and / or, the organic phosphonic acid compound is phosphoethanolamine, 2-aminoethylphosphonic acid, 3-aminopropylphosphonic acid or 4-aminobutylphosphonic acid; and / or, the molar ratio of the water-soluble polycarboxylic acid polymer to the organic phosphonic acid compound is 1:(6-150), preferably 1:(6-30), for example 1:6.62, 1:21.06, 1:21.77, 1:25.13 or 1:27.87; And / or, in step S1, the reaction raw materials further include a catalyst; the catalyst is preferably p-toluenesulfonic acid, concentrated sulfuric acid or methanesulfonic acid; the amount of the catalyst is preferably 0.5%-1.2% of the total mass of the water-soluble polycarboxylic acid polymer and the organic phosphonic acid compound; and / or, in step S1, the first temperature is 80-85°C, for example 80°C; And / or, in step S1, the reaction time is 1-3 h, such as 1 h or 2 h; And / or, in step S1, the vacuum degree of dehydration does not exceed -92 kPa, for example, -88 kPa, -90 kPa or -92 kPa; And / or, in step S1, the dehydration time is 1-2h; And / or, in step S2, the organic solvent is one or more of toluene, xylene, methyl pyrrolidone, propylene glycol methyl ether acetate, butyl acetate and N,N-dimethylformamide; and / or, in step S2, the second temperature is 100-120°C, such as 105°C, 110°C or 120°C; And / or, in step S2, the reaction time is 1-3 h, such as 1 h or 2 h; And / or, in step S2, the vacuum degree of dehydration does not exceed -92 kPa, for example, -88 kPa, -90 kPa or -92 kPa; And / or, in step S2, the dehydration time is 1-2h; And / or, in step S2, cooling is performed after dehydration; Preferably, the cooling temperature is 50°C or below; Preferably, after cooling, the material is discharged after neutralization with a neutralizer; More preferably, the neutralizing agent is one or more of lithium hydroxide, potassium hydroxide, sodium hydroxide, ethanolamine, diethanolamine, triethanolamine, isopropanolamine and 2-amino-2-methyl-1-propanol.

5. The method for preparing a comb polymer according to claim 3, characterized in that: The preparation method of the water-soluble polycarboxylic acid polymer comprises the following steps: in the presence of an initiator and a chain transfer agent, polymerizing the monomer M-1, the monomer M-2 and the monomer M-3 in a solvent; the monomer M-1 is a compound corresponding to the repeating unit I; the monomer M-2 is a compound corresponding to the repeating unit II; the monomer M-3 is a compound corresponding to the repeating unit III', or an acid anhydride formed by the compound corresponding to the repeating unit III'; Preferably, the mass of the monomer M-1 is 10%-69% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3, for example, 10%, 30%, 40%, 67% or 69%; Preferably, the monomer M-1 is an unsaturated terminated polyether; More preferably, the unsaturated terminated polyether is polyethylene glycol monomethyl ether methacrylate, methyl terminated methyl allyl alcohol polyoxyethylene ether, C 12 -C 14 Carbon alcohol polyoxyethylene ether methacrylate, C 12 -C 14 Carbon alcohol polyoxyethylene ether acrylate, isomeric tridecanol polyoxyethylene ether methacrylate, isomeric tridecanol polyoxyethylene ether acrylate, C1-C 18 Alkyl-terminated allyl alcohol polyoxyethylene ether, C1-C 18 Alkyl-terminated methyl allyl alcohol polyoxyethylene ether, C1-C 18 Alkyl-terminated allyl alcohol polyoxypropylene ether or C1-C 18 Alkyl terminated methyl allyl alcohol polyoxypropylene polyoxyethylene ether; More preferably, the average degree of polymerization of the polyether segments in the unsaturated terminated polyether is 7-10; Preferably, the molecular weight of the monomer M-1 is 300-1000, preferably 350-600, for example 350, 400 or 600; Preferably, the mass of the monomer M-2 is 1%-30% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3, for example, 1%, 3%, 5%, 10% or 30%; Preferably, the monomer M-2 is acrylonitrile, vinyl pyrrolidone, vinyl pyridine, vinyl imidazole or 2-acrylamido-2-methylpropane sulfonic acid; Preferably, the mass of the monomer M-3 is 30%-60% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3, for example, 30%, 55% or 60%; Preferably, the monomer M-3 is acrylic acid, methacrylic acid, maleic anhydride, itaconic acid, fumaric acid, crotonic acid or β-acryloxypropionic acid; Preferably, the initiator is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide and a water-soluble azo initiator; Preferably, the amount of the initiator is 0.1%-1% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3; Preferably, the chain transfer agent is at least one of isopropanol, mercaptoethanol, thioglycolic acid and mercaptopropionic acid; Preferably, the amount of the chain transfer agent is 0.1%-5% of the total mass of the monomer M-1, the monomer M-2 and the monomer M-3; Preferably, the initiator, the chain transfer agent, the monomer M-1, the monomer M-2 or the monomer M-3 are all added dropwise in the form of an aqueous solution; More preferably, the dripping time is 180-210 min; Preferably, the solvent is water; Preferably, the polymerization temperature is 65-85°C, such as 75°C or 80°C; Preferably, the polymerization time is 40-80 min, such as 60 min.

6. A comb polymer obtained by the method for preparing a comb polymer according to any one of claims 3 to 5.

7. An electrode slurry, characterized in that: It comprises the comb polymer according to any one of claims 1, 2 and 6.

8. The electrode slurry according to claim 7, characterized in that: Based on 100% of the total solid mass, the electrode slurry includes the following components in proportion by mass: 93%-98% of active material, 1%-4% of conductive agent, 1%-3% of binder and 0.1%-0.5% of the comb polymer; Preferably, the active material is one or more of lithium iron phosphate, lithium iron manganese phosphate and nickel-cobalt-manganese ternary material; Preferably, the conductive agent is one or more of conductive graphite, conductive carbon black and conductive carbon nanotubes; Preferably, the binder is PVDF.

9. An electrode plate, characterized in that: The electrode is prepared using the electrode slurry as claimed in claim 7 or 8.

10. A battery, characterized in that: It includes the electrode plate as claimed in claim 9.

Citation Information

Patent Citations

  • Composition for forming positive pole piece film layer, positive pole piece, preparation method of positive pole piece and secondary battery

    CN114551804A